The Effect of Verbal Plus Picture and Verbal only Information on Immediate Retention of Maritime Vocabulary - Budiman, Jeihn Novita Christanty; Ganap, Nindy Nource (Jayapangus Press, 2025)
English proficiency is a crucial skill for maritime professionals, as effective communication plays a significant role in ensuring safety and operational efficiency. However, acquiring and retaining maritime-specific vocabulary remains a challenge for many cadets. This study investigates the effectiveness of verbal-plus-picture and verbal-only instructional methods in enhancing the immediate retention of maritime English vocabulary. Additionally, it examines whether gender and prior English course experience influence vocabulary retention outcomes. Employing an experimental post-test research design, this study involved 200 cadets from Politeknik Pelayaran Sulawesi Utara, who were randomly assigned into two groups. The experimental group received instruction through a combination of verbal and pictorial learning approaches, while the control group received verbal-only instruction. A post-test was administered immediately after the intervention to measure vocabulary retention. Independent samples t-tests were conducted to compare the mean scores between the two groups, and multiple linear regression analysis was applied to evaluate the impact of gender and prior English course experience on vocabulary retention. The results indicate that cadets who received verbal-plus-picture instruction demonstrated significantly higher vocabulary retention compared to those in the verbal-only group (p-Value < 0.001). The mean post-test score for the experimental group was 67.65, while the control group scored 56.45, confirming the effectiveness of multimodal learning in maritime English education. However, gender and prior English course experience were found to have no statistically significant impact on vocabulary retention (p-Value = 0.500 and p-Value = 0.258, respectively). These findings support the Dual Coding Theory (DCT), which posits that integrating verbal and visual stimuli enhances learning and recall. The study highlights the importance of incorporating multimodal instructional strategies into maritime English training programs to optimize vocabulary acquisition.